BaTiO3 interlocking approaches in ZrO2 matrix - Pinto, João Pedro Figueiredo (2020)
Zirconia (ZrO2) is gaining interest for its high biocompatibility, high mechanical properties, inexistent ion release, and lower bacteria adhesion compared with titanium reducing the risk of marginal infiltrations. Barium titanate (BaTiO3) is also a very promising material for bone stimulation due to a high piezoelectric constant (191pC/N), lead-free without toxicological risk, and absence of foreign body reactions at the implant-tissue interface. In different load conditions, this material can improve bone ingrowth, for negative surface potentials and an antibacterial effect, for positive surface potentials. Implant infection is one of the most complications of postsurgical medical device implantation. In this study, the interface of BaTiO3-ZrO2 has been studied with particles dip-coated and full BaTiO3 addition in ZrO2 to access the viability of the two materials.